laminated polyester film
Patent Information
- Application Number
- KR1020227017571
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-10-29
- Filing Date
- 2020-10-23
- Publication Date
- 2026-09-15
- Estimated Expiration
- 2040-10-23
Smart Images

Figure 112022055119087-PCT00001
Abstract
Description
Technology Field
[0001] The present invention relates to a laminated polyester film. More specifically, it relates to a laminated polyester film having a coating layer with excellent adhesion properties, which is optimal for all fields such as optics, packaging, and labeling.
[0002] Thermoplastic resin films, particularly polyester films, are widely used in magnetic recording materials, packaging materials, optical films such as anti-reflective films, diffusion sheets, and prism sheets used in solar cells and flat displays, as well as label printing films, due to their excellent mechanical, electrical, dimensional stability, transparency, and chemical resistance. However, polyester films have a drawback in that their surfaces are highly crystallinely oriented, resulting in poor adhesion to various paints, resins, and inks during processing for these applications.
[0003] For this reason, various methods to impart adhesion to the surface of polyester films have been explored since the past.
[0004] Conventionally, as a method for imparting adhesion, surface activation methods such as corona discharge treatment, ultraviolet irradiation treatment, and plasma treatment are known for the surface of a polyester film to be used as a substrate. However, since the adhesion effect obtained by these treatments decreases over time, it was difficult to maintain a high level of adhesion over a long period. (Patent Document 1)
[0005] For this reason, a method of applying various resins to the surface of a polyester film to provide a coating layer with easy adhesion performance is frequently used.
[0006] Conventionally, a technology has been known to improve affinity with resin components such as polyurethane acrylate or ester acrylate used in hard coats and prism lenses, and to impart adhesion to them, by using a coating solution containing copolymer polyester resin or urethane resin, or a coating solution using the resin and a crosslinking agent in combination, in the coating layer (Patent Documents 2 and 3). However, in UV-curing inks used for label printing, dyes or pigments are contained in addition to the resin for color expression, and pigments with relatively good lightfastness are used in an amount of about 15 to 25 weight percent of the ink components. Furthermore, in white ink systems where opacity is important, the content of white pigment is high at about 50 weight percent, so the adhesion in the conventional technology is insufficient, and adhesion is particularly difficult under low radiation doses. Prior art literature
[0007] Japanese Patent Publication No. Sho 58-27724 Japanese Patent Publication No. 2000-229355 Japanese Patent Publication No. 2009-220376 The problem to be solved
[0008] The present invention was made against the background of the problems of the prior art. That is, the objective of the present invention is to provide a laminated polyester film that has good adhesion to UV-curable resins, particularly excellent adhesion to coating agents such as UV-curable inks, and excellent maintenance of a high level of adhesion over a long period of time. means of solving the problem
[0009] That is, the present invention includes the following configuration.
[0010] 1. A laminated polyester film having a coating layer formed of a composition comprising a polyurethane resin having an acid value of 30 to 50 mgKOH / g and having a carboxyl group on at least one side of the polyester film, and a crosslinking agent having an acid value of 30 to 50 mgKOH / g and having a carboxyl group.
[0011] 2. The first described laminated polyester film, wherein the crosslinking agent is an isocyanate-based compound. Effects of the invention
[0012] The laminated polyester film of the present invention has excellent adhesion to UV-curing resins such as hard coat layers, lens layers, and inks, but particularly exhibits excellent high-level adhesion to UV-curing inks. Specific details for implementing the invention
[0013] (Polyester film substrate)
[0014] In the present invention, the polyester resin constituting the polyester film substrate is a copolymer polyester resin in which a portion of the diol component or dicarboxylic acid component of the above polyester resin is substituted with the following copolymer component, in addition to polyethylene terephthalate, polybutylene terephthalate, polyethylene-2,6-naphthalate, polytrimethylene terephthalate, etc., and the copolymer component may include a diol component such as diethylene glycol, neopentyl glycol, 1,4-cyclohexanedimethanol, polyalkylene glycol, or a dicarboxylic acid component such as adipic acid, sebacic acid, phthalic acid, isophthalic acid, 5-sodium isophthalic acid, 2,6-naphthalene dicarboxylic acid.
[0015] The polyester resin suitably used for the polyester film substrate in the present invention is mainly selected from polyethylene terephthalate, polytrimethylene terephthalate, polybutylene terephthalate, and polyethylene-2,6-naphthalate. Among these polyester resins, polyethylene terephthalate is most preferred due to the balance of physical properties and cost. In addition, the polyester film substrate composed of these polyester resins is preferably a biaxially stretched polyester film, which can improve chemical resistance, heat resistance, mechanical strength, etc.
[0016] The catalyst for polycondensation used in the manufacture of polyester resin is not particularly limited, but antimony trioxide is suitable because it is inexpensive and has excellent catalytic activity. In addition, it is also desirable to use germanium compounds or titanium compounds. More preferred polycondensation catalysts include catalysts containing aluminum and / or its compounds and phenolic compounds, catalysts containing aluminum and / or its compounds and phosphorus compounds, and catalysts containing aluminum salts of phosphorus compounds.
[0017] In addition, the polyester film substrate in the present invention is not particularly limited in its layer composition, and may be a single-layer polyester film, a two-layer structure with different components, or a polyester film substrate comprising at least three layers having an outer layer and an inner layer.
[0018] (Coating layer)
[0019] In order to improve adhesion to a hard coat layer, adhesion to a UV-curable ink, and blocking resistance, the laminated polyester film of the present invention preferably has a coating layer laminated thereon on at least one side, the coating layer being formed from a polyurethane resin having a carboxyl group and an acid value of 30 to 50 mgKOH / g and a crosslinking agent having a carboxyl group and an acid value of 30 to 50 mgKOH / g. The coating layer may be provided on both sides of the polyester film, or it may be provided only on one side of the polyester film and a heterogeneous resin coating layer provided on the other side.
[0020] The coating layer in the present invention exhibits excellent adhesion to UV-curing resins or thermosetting resins, such as hard coat layers, lens layers, and inks, but is particularly excellent to inks containing pigments. This effect is presumed to be the result of the interaction between the carboxyl groups in the coating layer and the pigment particles in the ink. Furthermore, by having the polyurethane resin and the crosslinking agent each possess a certain range of carboxyl groups, it has become possible to incorporate a large number of carboxyl groups into the coating layer itself, while suppressing the occurrence of defects such as reduced water resistance and poor heat resistance caused by the individual resin having a large number of carboxyl groups.
[0021] The weight ratio of the polyurethane resin having carboxyl groups and the crosslinking agent having carboxyl groups is preferably in the range of 90 / 10 to 10 / 90, more preferably in the range of 80 / 20 to 20 / 80, and further preferably in the range of 70 / 30 to 30 / 70. If the crosslinking agent is insufficient, durability such as moisture and heat resistance is reduced, and if the polyurethane resin is insufficient, adhesion is reduced.
[0022] Below, the composition of each coating layer is explained in detail.
[0023] (Polyurethane resin having a carboxyl group and an acid value of 30 to 50 mgKOH / g)
[0024] A polyurethane resin having carboxyl groups is a urethane resin synthesized with at least a polyol component and a polyisocyanate component, and, if necessary, a chain extender, etc., and has carboxyl groups in the molecule or in the side chain. The term "in the molecule" as used herein refers to those present in the main chain or at the end of the above polyurethane resin. Furthermore, a side chain is one that is introduced onto a branched molecular chain after synthesis and polymerization by having three or more terminal functional groups of the raw material components of any of the above that constitute the molecular chain.
[0025] The polyurethane resin having carboxyl groups in the present invention is obtained mainly by using a carboxyl group-containing polyol component as a component of the urethane.
[0026] Examples of such carboxyl group-containing polyol components include the following. Relatively high molecular weight types may be used, such as carboxyl group-containing polyalkylene glycol, carboxyl group-containing acrylic polyol, carboxyl group-containing polyolefin polyol, carboxyl group-containing polyester polyol, etc. Additionally, relatively low molecular weight types may be used, such as 2,2-dimethylolpropionic acid, 2,2-dimethylolbutyric acid, 2,2-dimethylolvaleric acid, etc. Dimethylolpropionic acid and dimethylolbutyric acid are particularly suitable for introducing carboxyl groups.
[0027] The acid value of the polyurethane resin having carboxyl groups is preferably 30 to 50 mgKOH / g, and more preferably 35 to 45 mgKOH / g. If the acid value is 30 mgKOH / g or higher, the adhesion to UV-curable resins, particularly UV-curable inks, is improved. On the other hand, if the acid value is 50 mgKOH / g or lower, the water resistance of the coating layer is maintained, and it is preferable because there is no tendency for the films to stick together due to moisture absorption. However, in the polyurethane resin of the present invention, other hydrophilic groups, such as hydroxyl groups, ethers, sulfonic acids, phosphonic acids, quaternary amines, etc., may be introduced within a range that does not degrade performance in order to supplement the water solubility or water dispersibility of the polyurethane resin.
[0028] The carboxyl groups in the polyurethane resin may be neutralized with a basic compound. Examples of basic compounds used for neutralization include alkali metals such as sodium and potassium, alkaline earth metals such as magnesium and calcium, and organic amine compounds. Among these, organic amine compounds that easily dissociate from the carboxyl groups upon heating are preferred. Examples of organic amine compounds include, for instance, straight-chain or branched primary, secondary, or tertiary amines having 1 to 20 carbon atoms, such as ammonia, methylamine, ethylamine, propylamine, isopropylamine, butylamine, 2-ethylhexylamine, cyclohexylamine, dimethylamine, diethylamine, dipropylamine, diisopropylamine, dibutylamine, trimethylamine, triethylamine, triisopropylamine, tributylamine, and ethylenediamine; cyclic amines such as morpholine, N-alkylmorpholine, and pyridine; hydroxyl group-containing amines such as monoisopropanolamine, methylethanolamine, methylisopropanolamine, dimethylethanolamine, diisopropanolamine, diethanolamine, triethanolamine, diethylethanolamine, and triethanolamine.
[0029] In the other polyol component used to synthesize and polymerize the urethane resin in the present invention, polycarbonate polyol is preferably used, and it is particularly preferable to contain an aliphatic polycarbonate polyol with excellent heat resistance and hydrolysis resistance. Examples of aliphatic polycarbonate polyols include aliphatic polycarbonate diol and aliphatic polycarbonate triol, but aliphatic polycarbonate diol may suitably be used. Examples of aliphatic polycarbonate diols used to synthesize and polymerize a urethane resin having a polycarbonate structure in the present invention include, for instance, an aliphatic polycarbonate diol obtained by reacting one or more types of diols such as ethylene glycol, propylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, 1,9-nonanediol, 1,8-nonanediol, neopentyl glycol, diethylene glycol, and dipropylene glycol with carbonates such as, for instance, dimethyl carbonate, ethylene carbonate, and phosgene.
[0030] The number average molecular weight of the polycarbonate polyol described above in the present invention is preferably 300 to 5000. More preferably, it is 400 to 4000, and most preferably 500 to 3000. If it is 300 or higher, it is desirable as it can improve ink adhesion. If it is 3000 or lower, it is desirable as it can improve blocking resistance.
[0031] Examples of polyisocyanates used in the synthesis and polymerization of urethane resins in the present invention include aliphatic diisocyanates having an aromatic ring such as xylylene diisocyanate, alicyclic diisocyanates such as isophorone diisocyanate and 4,4-dicyclohexylmethane diisocyanate and 1,3-bis(isocyanatemethyl)cyclohexane, aliphatic diisocyanates such as hexamethylene diisocyanate and 2,2,4-trimethylhexamethylene diisocyanate, modified polyisocyanates containing isocyanurate bonds, biuret bonds, or allophanate bonds prepared from diisocyanates, and polyisocyanates in which a single or multiple diisocyanates are pre-added with trimethylolpropane, etc. It is desirable to use aliphatic diisocyanates, alicyclic diisocyanates, or aliphatic diisocyanates having the aforementioned aromatic ring, as there is no problem with yellowing.
[0032] Examples of chain extenders include glycols such as ethylene glycol, diethylene glycol, 1,4-butanediol, neopentyl glycol, and 1,6-hexanediol; polyhydric alcohols such as glycerin, trimethylolpropane, and pentaerythritol; diamines such as ethylenediamine, hexamethylenediamine, and piperazine; amino alcohols such as monoethanolamine and diethanolamine; thiodiglycols such as thiodiethylene glycol; or water. In addition, if used in small amounts, polyols with three or more functional groups, polyamines, etc. may be used.
[0033] The polyurethane resin of the present invention may have reactive groups, such as block isocyanates, at the terminals or side chains to improve rigidity.
[0034] (Crosslinking agent)
[0035] In the present invention, a crosslinking agent having a carboxyl group and an acid value of 30 to 50 mgKOH / g is used. Additionally, the carboxyl group of the crosslinking agent may be neutralized with a basic compound, similar to the polyurethane resin described above. The acid value of the crosslinking agent having a carboxyl group is preferably 30 to 50 mgKOH / g, and more preferably 35 to 45 mgKOH / g. An acid value of 30 mgKOH / g or higher is desirable because it improves adhesion to UV-curable resins, particularly UV-curable inks. On the other hand, an acid value of 50 mgKOH / g or lower is desirable because the water resistance of the coating layer after coating is maintained, and there is no risk of the film easily sticking together due to moisture absorption. However, to supplement the water solubility or water dispersibility of the crosslinking agent in the present invention, other hydrophilic groups, such as hydroxyl groups, ethers, sulfonic acids, phosphonic acids, quaternary amines, etc., may be introduced within a range that does not degrade performance.
[0036] Examples of crosslinking agents having carboxyl groups include oxazoline compounds, carbodiimide compounds, epoxy compounds, and isocyanate compounds in which carboxyl groups have been introduced into the molecule. Additionally, it is possible to pre-neutralize the carboxyl groups with a basic compound so that they do not react within or between molecules. Among these crosslinking agents, isocyanate compounds that facilitate the easy introduction of carboxyl groups into the molecule are preferred, and block isocyanate compounds are particularly preferred.
[0037] Examples of blocking agents include bisulfite compounds such as sodium bisulfite, pyrazole compounds such as 3,5-dimethylpyrazole, 3-methylpyrazole, 4-bromo-3,5-dimethylpyrazole, and 4-nitro-3,5-dimethylpyrazole, phenolic compounds such as phenol and cresol, aliphatic alcohol compounds such as methanol and ethanol, active methylene compounds such as dimethyl malonicate and acetylacetone, mercaptan compounds such as butyl mercaptan and dodecyl mercaptan, acid amide compounds such as acetanilide and acetamide, lactam compounds such as ε-caprolactam and δ-valerolactam, acid imide compounds such as succinate imide and maleate imide, oxime compounds such as acetaldoxime, acetone oxime, and methyl ethyl ketoxime, and amine compounds such as diphenylaniline, aniline, and ethyleneimine.
[0038] The lower limit of the boiling point of the blocking agent of the above-mentioned block isocyanate is preferably 150°C, more preferably 160°C, even more preferably 180°C, particularly preferably 200°C, and most preferably 210°C. The higher the boiling point of the blocking agent, the more the volatilization of the blocking agent is suppressed by heat application during the drying process after the coating solution application or, in the case of the inline coating method, during the film formation process; consequently, the occurrence of minute irregularities on the coated surface is suppressed, and the transparency of the film is improved. Although the upper limit of the boiling point of the blocking agent is not specifically limited, it is considered that the upper limit is around 300°C in terms of productivity. Since the boiling point is related to molecular weight, in order to increase the boiling point of the blocking agent, it is desirable to use a blocking agent with a large molecular weight; the molecular weight of the blocking agent is preferably 50 or higher, more preferably 60 or higher, and even more preferably 80 or higher.
[0039] The upper limit of the dissociation temperature of the blocking agent is preferably 200°C, more preferably 180°C, even more preferably 160°C, particularly preferably 150°C, and most preferably 120°C. The blocking agent dissociates due to heat addition during the drying process after the application of the coating solution or, in the case of the inline coating method, during the film formation process, and regenerated isocyanate groups are generated. Consequently, a cross-linking reaction with urethane resin, etc., proceeds, and adhesion is improved. When the dissociation temperature of the block isocyanate is below the above temperature, the dissociation of the blocking agent proceeds sufficiently, so adhesion, particularly resistance to moisture and heat, becomes good.
[0040] Examples of blocking agents used in the block isocyanate of the present invention, wherein the dissociation temperature is 120°C or lower and the boiling point of the blocking agent is 150°C or higher, include the aforementioned sodium bisulfite, 3,5-dimethylpyrazole, 3-methylpyrazole, dimethyl malonicate, diethyl malonicate, acetone oxime, methyl ethyl ketoxime, etc. Among these, pyrazole-based compounds represented by 3,5-dimethylpyrazole and 3-methylpyrazole are preferred in terms of resistance to humid heat and yellowing.
[0041] The above-mentioned block isocyanate is preferably difunctional or more, and a block isocyanate with trifunctional or more is even more preferable in terms of the crosslinkability of the coating film.
[0042] Polyisocyanates with three or more functional groups, which are precursors of the block isocyanates of the present invention, can be suitably obtained by introducing isocyanate monomers. For example, biuret bodies, isocyanurate bodies, and adduct bodies obtained by modifying isocyanate monomers such as aromatic diisocyanates, aliphatic diisocyanates, aromatic aliphatic diisocyanates, or alicyclic diisocyanates having two isocyanate groups can be used.
[0043] A biuret group is a self-condensed product having a biuret bond formed by the self-condensation of isocyanate monomers, and examples include the biuret group of hexamethylene diisocyanate.
[0044] Isocyanurates are trimers of isocyanate monomers, such as the trimer of hexamethylene diisocyanate, the trimer of isophorone diisocyanate, and the trimer of tolylene diisocyanate.
[0045] An adduct refers to an isocyanate compound with three or more functions formed by reacting an isocyanate monomer with a low molecular weight active hydrogen-containing compound with three or more functions. Examples include a compound formed by reacting trimethylolpropane with hexamethylene diisocyanate, a compound formed by reacting trimethylolpropane with tolylene diisocyanate, a compound formed by reacting trimethylolpropane with xylylene diisocyanate, a compound formed by reacting trimethylolpropane with isophorone diisocyanate, etc.
[0046] As the above-mentioned isocyanate monomers, 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, 4,4'-diphenylmethane diisocyanate, 2,4'-diphenylmethane diisocyanate, 2,2'-diphenylmethane diisocyanate, 1,5-naphthylene diisocyanate, 1,4-naphthylene diisocyanate, phenylene diisocyanate, tetramethylxylylene diisocyanate, 4,4'-diphenyl ether diisocyanate, 2-nitrodiphenyl-4,4'-diisocyanate, 2,2'-diphenylpropane-4,4'-diisocyanate, 3,3'-dimethyldiphenylmethane-4,4'-diisocyanate, 4,4'-diphenylpropane diisocyanate, Examples include aromatic diisocyanates such as 3,3'-dimethoxydiphenyl-4,4'-diisocyanate and xylylene diisocyanate, alicyclic diisocyanates such as isophorone diisocyanate and 4,4-dicyclohexylmethane diisocyanate and 1,3-bis(isocyanatemethyl)cyclohexane, and aliphatic diisocyanates such as hexamethylene diisocyanate and 2,2,4-trimethylhexamethylene diisocyanate. Aliphatic and alicyclic isocyanates or modified bodies thereof are preferred in terms of transparency, resistance to yellowing, adhesion, and resistance to moisture and heat.
[0047] In the present invention, other resins may be used in combination within a range that does not affect performance. Examples of resins used in combination include carboxyl group-free polyurethane, polyester resin, acrylic resin, cellulose resin, polyolefin resin, polyacetal resin, etc. Among these resins, polyester resin is particularly preferred as its adhesion to the UV-curing resin is improved by combination. Furthermore, when polyester resin is used in combination, it is possible to include at least 1.5 times the combined content of the carboxyl group-containing polyurethane resin and the carboxyl group-containing crosslinking agent. It is speculated that this effect is due to the fact that the polyester resin has better affinity for the substrate polyester resin than the carboxyl group-containing polyurethane resin or the carboxyl group-containing crosslinking agent, so it is easy to localize to the substrate side in the thickness direction, thereby improving adhesion to the substrate interface, and the carboxyl group-containing polyurethane resin and the carboxyl group-containing crosslinking agent localized to the surface layer exhibit a synergistic effect that improves adhesion to the UV-cured resin.
[0048] (Polyester resin)
[0049] The polyester resin used in combination with the coating layer in the present invention may be a straight-chain type, but more preferably, it is a polyester resin having a dicarboxylic acid and a diol (glycol) having a branched structure or a diol containing one or more ether bonds as constituent components. The dicarboxylic acid referred to herein may include aliphatic dicarboxylic acids such as adipic acid and sebacic acid, whose main components are terephthalic acid, isophthalic acid, or 2,6-naphthalenedicarboxylic acid, as well as aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, phthalic acid, and 2,6-naphthalenedicarboxylic acid. In addition, the branched glycol is a diol having a branched alkyl group, for example, 2,2-dimethyl-1,3-propanediol, 2-methyl-2-ethyl-1,3-propanediol, 2-methyl-2-butyl-1,3-propanediol, 2-methyl-2-propyl-1,3-propanediol, 2-methyl-2-isopropyl-1,3-propanediol, 2-methyl-2-n-hexyl-1,3-propanediol, 2,2-diethyl-1,3-propanediol, 2-ethyl-2-n-butyl-1,3-propanediol, 2-ethyl-2-n-hexyl-1,3-propanediol, 2,2-di-n-butyl-1,3-propanediol, 2-n-butyl-2-propyl-1,3-propanediol, and Examples include 2,2-di-n-hexyl-1,3-propanediol.
[0050] In addition, examples of diols containing one or more ether bonds include condensates of alkylene glycols such as diethylene glycol, triethylene glycol, and dipropylene glycol, and ethylene oxide or propylene oxide adducts of bisphenols. Although there is no particular limit on the number of ether bonds in the molecule, it is preferable to have four or fewer, and furthermore two or fewer, because the strength or glass transition point of the polyester resin is reduced.
[0051] With respect to the polyester resin above, the branched glycol component or the diol component containing one or more ether bonds, which is a more preferred embodiment of the above, may be contained in the total glycol component in a ratio of preferably 10 mol% or more, and more preferably 20 mol% or more. If it is 10 mol% or more, it is desirable that the crystallinity does not become too high and the adhesion of the coating layer is maintained. The upper limit of the glycol component in the total glycol component is preferably 80 mol% or less, and more preferably 70 mass% or less. If it is 80 mol% or less, it is desirable that the concentration of the byproduct oligomer is difficult to increase, and the transparency of the coating layer is maintained. Ethylene glycol is most preferred as a glycol component other than the above compound. In small amounts, propylene glycol, butanediol, hexanediol, or 1,4-cyclohexanedimethanol, etc., may be used.
[0052] As a dicarboxylic acid for the constituent of the above polyester resin, it is most preferable to use terephthalic acid or isophthalic acid. In addition to the above dicarboxylic acid, in order to impart water dispersibility to the copolymerized polyester resin, it is preferable to copolymerize 5-sulfoisophthalic acid, etc. in a range of 1 to 10 mol%, and examples include sulfoterephthalic acid, 5-sulfoisophthalic acid, 5-sodium sulfoisophthalic acid, etc.
[0053] When the total solid content of the resin and crosslinking agent in the coating solution forming the coating layer is set to 100 mass%, it is desirable that the polyester resin content be 10 mass% or more, as this improves the adhesion between the coating layer and the polyester film substrate. The upper limit of the polyester resin content is preferably 65 mass% or less, and more preferably 60 mass% or less. It is desirable that the polyester resin content be 70 mass% or less, as this improves the moisture and heat resistance after ink processing.
[0054] Among the coating layers, resins other than the aforementioned polyester resin may also be used within a range that does not degrade the performance of the present invention. A representative example of a resin other than the polyester resin is a polyurethane resin having carboxyl groups, but it may include other resins, or it may consist solely of a polyurethane resin having carboxyl groups.
[0055] In that case, if the total solid content of the resin and crosslinking agent in the coating solution forming the coating layer is 100 mass%, the content of the resin other than the polyester resin is preferably 40 mass% or less, more preferably 30 mass% or less, and particularly preferably 20 mass% or less. However, the total content of the resin other than the polyester resin and the polyester resin is preferably 70 mass% or less. The respective content of the aforementioned polyurethane resin and crosslinking agent in the coating solution forming the coating layer is preferably 3 mass% or more as the total solid content of the resin and crosslinking agent.
[0056] It is desirable that the content be 3 mass% or more, as this provides adhesion to UV-curing resins and adhesion to coating agents such as UV-curing inks. A more desirable range of content is 3.5 to 90 mass%, 7 to 80 mass% is more desirable, and 10.5 to 70 mass% is particularly desirable.
[0057] (Additives)
[0058] In the coating layer of the present invention, known additives, such as surfactants, antioxidants, heat stabilizers, weather stabilizers, ultraviolet absorbers, organic activators, pigments, dyes, organic or inorganic particles, antistatic agents, nucleating agents, etc., may be added to a range that does not impede the effects of the present invention.
[0059] In the present invention, it is a preferred embodiment to add particles to the coating layer in order to further improve the anti-blocking properties of the coating layer. Examples of particles included in the coating layer in the present invention include titanium oxide, barium sulfate, calcium carbonate, calcium sulfate, silica, alumina, talc, kaolin, clay, etc., or mixtures thereof, and other general inorganic particles such as calcium phosphate, mica, hectorite, zirconia, tungsten oxide, lithium fluoride, calcium fluoride, etc., used in combination with others, or organic polymer particles such as styrene-based, acrylic-based, melamine-based, benzoguanamine-based, and silicon-based particles.
[0060] The average particle size of the particles in the coating layer (average particle size based on the number of particles by scanning electron microscope (SEM); hereinafter the same) is preferably 0.04 to 2.0 μm, and more preferably 0.1 to 1.0 μm. If the average particle size of the inert particles is 0.04 μm or more, it is desirable because the formation of irregularities on the film surface is facilitated, thereby improving handling properties such as the slipperiness and windability of the film and ensuring good processability during bonding. On the other hand, if the average particle size of the inert particles is 2.0 μm or less, it is desirable because particle detachment is less likely to occur. The particle concentration in the coating layer is preferably 1 to 20 mass% of the solid component.
[0061] The method for measuring the average particle size of the particles was performed by observing cross-sectional particles of a laminated polyester film using a scanning electron microscope, observing 30 particles, and taking the average value as the average particle size.
[0062] As long as it satisfies the purpose of the present invention, the shape of the particles is not particularly limited, and spherical particles or irregular non-spherical particles may be used. The particle diameter of irregular particles can be calculated as the diameter equivalent to a circle. The diameter equivalent to a circle is the value obtained by dividing the observed particle area by π, calculating the square root, and multiplying it.
[0063] (Manufacture of laminated polyester film)
[0064] Regarding the method for manufacturing a laminated polyester film of the present invention, an example using a polyethylene terephthalate (hereinafter abbreviated as PET) film substrate is described, but it is not, of course, limited thereto.
[0065] After sufficiently vacuum drying the PET resin, it is supplied to an extruder, and the molten PET resin at approximately 280°C from the T-die is melt-extruded into a sheet shape onto a rotary cooling roll, and then cooled and solidified by an electrostatic method to obtain an unoriented PET sheet. The unoriented PET sheet may be composed of a single layer or a multilayer structure formed by a co-extrusion method.
[0066] The obtained unoriented PET sheet is crystallinely oriented by performing uniaxial or biaxial stretching. For example, in the case of biaxial stretching, the film is stretched 2.5 to 5.0 times in the longitudinal direction on a roll heated to 80 to 120°C to obtain a uniaxially stretched PET film, then the end of the film is clipped and guided into a hot air zone heated to 80 to 180°C to stretch it 2.5 to 5.0 times in the width direction. In the case of uniaxial stretching, the film is stretched 2.5 to 5.0 times in a tenter. After stretching, the film is subsequently guided into a heat treatment zone and heat treatment is performed to complete the crystalline orientation.
[0067] The lower limit of the temperature of the heat treatment zone is preferably 170°C, and more preferably 180°C. If the temperature of the heat treatment zone is 170°C or higher, sufficient curing is achieved and blocking properties in the presence of liquid water are improved, which is desirable, and there is no need to extend the drying time. Meanwhile, the upper limit of the temperature of the heat treatment zone is preferably 250°C, and more preferably 240°C. If the temperature of the heat treatment zone is 240°C or lower, it is desirable as there is no risk of the physical properties of the film deteriorating.
[0068] The coating layer can be prepared after the manufacture of the film or during the manufacturing process. In particular, for the sake of productivity, it is preferable to apply a coating solution to at least one side of a PET film after any stage of the film manufacturing process, namely after unoriented or uniaxial stretching, and then stretch and heat treat the film in at least one axial direction to form a coating layer.
[0069] Any known method may be used to apply this coating solution to a PET film. Examples include the reverse roll coating method, gravure coating method, kiss coating method, die coater method, roll brush method, spray coating method, air knife coating method, wire bar coating method, pipe doctor method, impregnation coating method, curtain coating method, etc. These methods may be used for coating alone or in combination.
[0070] In the present invention, the thickness of the coating layer can be appropriately set within a range of 0.001 to 2.00 μm, but to achieve both processability and adhesion, a range of 0.01 to 1.00 μm is preferred, more preferably 0.02 to 0.80 μm, and even more preferably 0.05 to 0.50 μm. It is preferable that the thickness of the coating layer be 0.001 μm or more because the adhesion is good. It is preferable that the thickness of the coating layer be 2.00 μm or less because it is difficult to cause blocking.
[0071] The upper limit of the haze of the laminated polyester film of the present invention is preferably 2.5%, more preferably 2.0%, even more preferably 1.5%, and particularly preferably 1.2%. If the haze is 2.5% or less, it is desirable in terms of transparency, and thus can be suitably used in optical films where transparency is required. In general, it is preferable for the haze to be smaller, but it is also preferable for it to be 0.1% or more, and 0.2% or more.
[0072] Examples
[0073] Next, the present invention will be described in detail using examples and comparative examples, but the present invention is not limited to the following examples. First, the evaluation method used in the present invention will be described below.
[0074] (1) Hayes
[0075] The haze of the obtained laminated polyester film was measured using a turbidimeter (Nippon Denshoku, NDH5000) in accordance with JIS K 7136:2000.
[0076] (2) Acidity
[0077] The acid values of the resin and crosslinking agent were measured by the titration method described in JIS K1557-5:2007.
[0078] However, in the case of carboxyl groups neutralized with amines, the amines were removed by high-temperature treatment, or the amines were liberated and removed by prior treatment with hydrochloric acid before measurement. In addition, in the case of crosslinking agents, the reactive groups such as isocyanates were reacted with amines before measurement. If the resin being measured had poor solubility in the solvent isopropanol, N-methylpyrrolidone was used instead. In any of the above treatments, sufficient comparative measurements were performed.
[0079] (3) Blocking resistance
[0080] Two film samples were overlapped with the coated layers facing each other, a load of 98 kPa was applied, and the samples were kept in contact for 24 hours under an atmosphere of 50°C and left to stand. Afterward, the films were peeled off, and the peeling state was judged according to the following criteria.
[0081] ○: There is no transfer of the coating layer, and it can be easily peeled off.
[0082] △: The coating layer is maintained, but the surface layer of the coating layer is partially transferred to the opposite surface.
[0083] ×: Two films are bonded together and do not peel off, or even if peeled off, the film substrate is separated.
[0084] (4) Adhesion with UV-curing ink
[0085] A UV-curing ink [manufactured by T&K TOKA Co., Ltd., product name "BEST CURE UV161 Indigo S" or "BEST CURE UV161 White S"] was used on the coating layer of a laminated polyester film, and printing was performed using a printing press [manufactured by Seisakusho Co., Ltd., product name "RI Tester"] with an ink pipette of 4 divisions and a 2-split roll. Subsequently, ultraviolet light of 100 or 40 mJ / cm² was irradiated onto the film coated with the ink layer using a high-pressure mercury lamp to cure the UV-curing ink. Next, using a cutter guide with a gap of 2 mm, 100 grid-like cut marks were engraved on the ink layer surface, penetrating the ink layer and reaching the film substrate. Subsequently, cellophane adhesive tape (Nichiban No. 405; 24 mm width) was firmly attached to the grid-like cut marks. Subsequently, the cellophane adhesive tape is peeled vertically from the ink layer surface of the ink laminated film, and the number of grid squares peeled off from the ink layer surface of the ink laminated film is visually counted to determine the adhesion between the ink layer and the film substrate using the following formula. In addition, partially peeled grid squares are also counted as peeled grid squares, and the ink adhesion is determined using the following formula.
[0086] Ink adhesion (%) = 100 - (number of peeled grid squares)
[0087] Ink adhesion was evaluated based on the following criteria.
[0088] ◎: 100%, ○: 96 to 99%, △: 80 to 95%, ×: Less than 80%
[0089] Based on the criteria, anything above ○ was considered a pass.
[0090] (5) Adhesion to the hard coat layer
[0091] A UV-curing hard coat agent, Opster Z7503 (manufactured by Arakawa Kagaku Kogyo Co., Ltd.), was applied onto a coating layer of a laminated polyester film using a #5 wire bar and dried at 80°C for 1 minute. Subsequently, the coated film was irradiated with ultraviolet rays of 100 mJ / ㎠ using a high-pressure mercury lamp, and a hard coat film with a hard coat layer thickness of 4 μm was obtained.
[0092] Next, using a cutter guide with a gap of 2 mm, 100 grid-like cut marks are engraved on the surface of the hard coat layer, penetrating the hard coat layer and reaching the film substrate. Then, a cellophane adhesive tape (Nichiban No. 405; 24 mm width) is applied to the grid-like cut marks and firmly attached. Afterward, the cellophane adhesive tape is pulled vertically from the surface of the hard coat layer of the hard coat laminated film. After performing the adhesive tape peeling operation a total of 5 times at the same location, the number of grid-like squares peeled off from the surface of the hard coat layer of the hard coat laminated film is visually counted, and the adhesion between the hard coat layer and the film substrate is calculated using the following formula. In addition, those grid-like squares that are partially peeled are also counted as peeled grid-like squares, and the hard coat adhesion is calculated as shown in the following formula.
[0093] Hard coat adhesion (%) = 100 - (number of peeled grid squares)
[0094] Hard coat adhesion was judged based on the following criteria.
[0095] ◎: 100%, ○: 96 to 99%, △: 80 to 95%, ×: Less than 80%
[0096] Based on the criteria, anything above ○ was considered a pass.
[0097] (6) Moisture resistance
[0098] A UV-curable ink coating film (a product cured at 100 mJ / ㎠ after UV irradiation following application of BEST CURE UV161 White S) or a hard coat coating film prepared in the same manner as (4) and (5) above was left for 500 hours with the coating surface positioned vertically and without contact with other films, etc., on the coating surface under an environment of 80°C and 80%RH. After treatment, the film was left for 10 minutes under an environment of 23°C and 65%RH with no contact with other films, etc., on the coating surface. Immediately after the time elapsed, the adhesion of the coating surface was evaluated in the same manner as described above.
[0099] (Polyurethane resin A-1 polymerization)
[0100] In a four-necked flask equipped with a stirrer, a dim loss condenser, a nitrogen inlet tube, a silica gel drying tube, and a thermometer, 82.8 parts by mass of hydrogenated m-xylylene diisocyanate, 25.0 parts by mass of dimethylolpropionic acid, 21.0 parts by mass of 1,6-hexanediol, 150.0 parts by mass of a polyesterdiol with a number average molecular weight of 2000 comprising adipic acid and 1,4-butanediol, and 110 parts by mass of methyl ethyl ketone as a solvent were added, and the mixture was stirred at 75°C for 3 hours under a nitrogen atmosphere, and it was confirmed that the reaction mixture had reached a predetermined amine equivalent. Subsequently, the temperature of the reaction mixture was lowered to 40°C, and 19.8 parts by mass of triethylamine were added to obtain a polyurethane polymer solution. Next, 500g of water is added to a reaction vessel equipped with a high-speed stirring homodisper, adjusted to 25℃, and 2000 min -1 While stirring and mixing, a polyurethane polymer solution was added and dispersed in water. Then, under reduced pressure, the solvent, methyl ethyl ketone, was removed. By adjusting the concentration with water, a solution containing 35 mass% of solids was prepared, which includes a polyurethane resin (A-1) with an acid value of 37.5 mgKOH / g.
[0101] (Polyurethane resin A-2 polymerization)
[0102] In a four-necked flask equipped with a stirrer, a dim loss condenser, a nitrogen inlet tube, a silica gel drying tube, and a thermometer, 63.0 parts by mass of hydrogenated m-xylylene diisocyanate, 21.0 parts by mass of dimethylolpropionic acid, 147.0 parts by mass of polycarbonate diol (1,6-hexanediol type) with a number average molecular weight of 2000, and 110 parts by mass of methyl ethyl ketone as a solvent were added. The mixture was stirred at 75°C for 3 hours under a nitrogen atmosphere, and it was confirmed that the reaction solution had reached a predetermined amine equivalent. Subsequently, the temperature of this reaction solution was lowered to 40°C, and 16.6 parts by mass of triethylamine was added to obtain a polyurethane polymer solution. Then, 500g of water was added to a reaction vessel equipped with a high-speed stirring homodisperser, the temperature was adjusted to 25°C, and 2000 min -1 While stirring and mixing, a polyurethane polymer solution was added and dispersed in water. Then, under reduced pressure, the solvent, methyl ethyl ketone, was removed. By adjusting the concentration with water, a solution containing 35 mass% of solids was prepared, which includes a polyurethane resin (A-2) with an acid value of 36.3 mgKOH / g.
[0103] (Polyurethane resin A-3 polymerization)
[0104] In a four-necked flask equipped with a stirrer, a dimrose condenser, a nitrogen inlet tube, a silica gel drying tube, and a thermometer, 64.5 parts by mass of hydrogenated diphenylmethane diisocyanate, 21.5 parts by mass of dimethylolpropionic acid, 11.2 parts by mass of neopentyl glycol, 150.5 parts by mass of polycarbonate diol (1,6-hexanediol type) with a number average molecular weight of 2000, and 110 parts by mass of methyl ethyl ketone as a solvent were added, and the mixture was stirred at 75°C for 3 hours under a nitrogen atmosphere, and it was confirmed that the reaction solution had reached a predetermined amine equivalent. Subsequently, the temperature of this reaction solution was lowered to 40°C, and 17.0 parts by mass of triethylamine was added to obtain a polyurethane polymer solution. Next, 500g of water is added to a reaction vessel equipped with a high-speed stirring homodisper, adjusted to 25℃, and 2000 min -1While stirring and mixing, a polyurethane polymer solution was added and dispersed in water. Then, under reduced pressure, the solvent, methyl ethyl ketone, was removed. By adjusting the concentration with water, a solution containing 35 mass% of solids was prepared, which included a polyurethane resin (A-3) with an acid value of 36.0 mgKOH / g.
[0105] (Polyurethane resin A-4 polymerization)
[0106] In a four-necked flask equipped with a stirrer, a dim loss condenser, a nitrogen inlet tube, a silica gel drying tube, and a thermometer, 83.4 parts by mass of hydrogenated m-xylylene diisocyanate, 16.9 parts by mass of dimethylolpropionic acid, 28.4 parts by mass of 1,6-hexanediol, 151.0 parts by mass of a polyesterdiol with a number average molecular weight of 2000 comprising adipic acid and 1,4-butanediol, and 110 parts by mass of methyl ethyl ketone as a solvent were added, and the mixture was stirred at 75°C for 3 hours under a nitrogen atmosphere, and it was confirmed that the reaction mixture had reached a predetermined amine equivalent. Subsequently, the temperature of this reaction mixture was lowered to 40°C, and 13.3 parts by mass of triethylamine were added to obtain a polyurethane polymer solution. Next, 500g of water is added to a reaction vessel equipped with a high-speed stirring homodisper, adjusted to 25℃, and 2000 min -1 A polyurethane polymer solution was added and dispersed in water while stirring and mixing. Then, the solvent, methyl ethyl ketone, was removed under reduced pressure. By adjusting the concentration with water, a solution containing 35 mass% of solids was prepared, which included a polyurethane resin (A-4) with an acid value of 25.3 mgKOH / g.
[0107] (Polyurethane resin A-5 polymerization)
[0108] In a four-necked flask equipped with a stirrer, a dimrose condenser, a nitrogen inlet tube, a silica gel drying tube, and a thermometer, 104.9 parts by mass of hydrogenated m-xylylene diisocyanate, 41.8 parts by mass of dimethylolpropionic acid, 19.0 parts by mass of 1,6-hexanediol, 152.0 parts by mass of a polyesterdiol with a number average molecular weight of 2000 comprising adipic acid and 1,4-butanediol, and 110 parts by mass of methyl ethyl ketone as a solvent were added, and the mixture was stirred at 75°C for 3 hours under a nitrogen atmosphere, and it was confirmed that the reaction mixture had reached a predetermined amine equivalent. Subsequently, the temperature of the reaction mixture was lowered to 40°C, and 33.1 parts by mass of triethylamine were added to obtain a polyurethane polymer solution. Next, 500g of water is added to a reaction vessel equipped with a high-speed stirring homodisper, adjusted to 25℃, and 2000 min -1 While stirring and mixing, a polyurethane polymer solution was added and dispersed in water. Then, under reduced pressure, the solvent, methyl ethyl ketone, was removed. By adjusting the concentration with water, a solution containing 35 mass% of solids was prepared, which includes a polyurethane resin (A-5) with an acid value of 55.0 mgKOH / g.
[0109] (Polyurethane resin A-6 polymerization)
[0110] 45.0 parts by mass of hydrogenated m-xylylene diisocyanate, 20.0 parts by mass of 1,6-hexanediol, 149.0 parts by mass of polyethylene glycol with a number average molecular weight of 2000, and 110 parts by mass of methyl ethyl ketone as a solvent were added to a four-necked flask equipped with a stirrer, a dim loss condenser, a nitrogen inlet tube, a silica gel drying tube, and a thermometer. The mixture was stirred at 75°C for 3 hours under a nitrogen atmosphere, and it was confirmed that the reaction mixture had reached a predetermined amine equivalent. Subsequently, the reaction mixture was cooled to 40°C, and 500g of water was added to a reaction vessel equipped with a high-speed stirring homodisperser. The temperature was adjusted to 25°C, and 2000 min -1While stirring and mixing, a polyurethane polymer solution was added and dispersed in water. Then, under reduced pressure, the solvent, methyl ethyl ketone, was removed. By adjusting the concentration with water, a solution containing 35 mass% of solids was prepared, which includes a polyurethane resin (A-6) with an acid value of 0.2 mgKOH / g.
[0111] (Polyurethane resin A-7 polymerization)
[0112] In a four-necked flask equipped with a stirrer, a dimrose condenser, a nitrogen inlet tube, a silica gel drying tube, and a thermometer, 43.8 parts by mass of hydrogenated diphenylmethane diisocyanate, 12.9 parts by mass of dimethylolbutanoic acid, 153.4 parts by mass of polycarbonate diol (1,6-hexanediol type) with a number average molecular weight of 2000, and 110 parts by mass of methyl ethyl ketone as a solvent were added. The mixture was stirred at 75°C for 3 hours under a nitrogen atmosphere, and it was confirmed that the reaction solution had reached a predetermined amine equivalent. Subsequently, the temperature of this reaction solution was lowered to 40°C, and 8.8 parts by mass of triethylamine was added to obtain a polyurethane polymer solution. Then, 500g of water was added to a reaction vessel equipped with a high-speed stirring homodisperser, the temperature was adjusted to 25°C, and 2000 min -1 While stirring and mixing, a polyurethane polymer solution was added and dispersed in water. Then, under reduced pressure, the solvent, methyl ethyl ketone, was removed. By adjusting the concentration with water, a solution containing 35 mass% of solids was prepared, which includes a polyurethane resin (A-7) with an acid value of 23.1 mgKOH / g.
[0113] (Polyurethane resin A-8 polymerization)
[0114] In a four-necked flask equipped with a stirrer, a dimrose condenser, a nitrogen inlet tube, a silica gel drying tube, and a thermometer, 68.0 parts by mass of hydrogenated diphenylmethane diisocyanate, 19.8 parts by mass of dimethylolpropionic acid, 148.0 parts by mass of polycarbonate diol (1,6-hexanediol type) with a number average molecular weight of 2000, and 110 parts by mass of methyl ethyl ketone as a solvent were added. The mixture was stirred at 75°C for 2 hours under a nitrogen atmosphere, and it was confirmed that the reaction mixture had reached a predetermined amine equivalent. Subsequently, 6.6 parts by mass of 2-butanone oxime were added, and the reaction was stirred for another 1 hour. After cooling the reaction mixture to 40°C, 15.7 parts by mass of triethylamine were added to obtain a polyurethane polymer solution. Next, 500g of water is added to a reaction vessel equipped with a high-speed stirring homodisper, adjusted to 25℃, and 2000 min -1 While stirring and mixing, a polyurethane polymer solution was added and dispersed in water. 1.1 parts by mass of a 10 mass% aqueous ethylenediamine solution were added while stirring. Afterward, the solvent, methyl ethyl ketone, was removed under reduced pressure. By adjusting the concentration with water, a solution with a solid content of 35 mass% containing a polyurethane resin (A-8) with an acid value of 32.0 mgKOH / g was prepared.
[0115] (Synthesis of crosslinking agent B-1)
[0116] 59.5 parts by mass of hexamethylene diisocyanate, 10.7 parts by mass of neopentyl glycol, 11.0 parts by mass of dimethylolbutanoic acid, and 20.0 parts by mass of N-methylpyrrolidone as a solvent were added to a flask equipped with a stirrer, a thermometer, and a reflux condenser, and the mixture was stirred at 80°C for 3 hours under a nitrogen atmosphere, and it was confirmed that the reaction mixture had reached a predetermined amine equivalent. Subsequently, 29.9 parts by mass of 2-butanone oxime were added dropwise to the reaction mixture, and the mixture was maintained at 80°C for 1 hour under a nitrogen atmosphere. Afterward, the infrared spectrum of the reaction mixture was measured, and after confirming that the absorption of the isocyanate group had disappeared, the temperature of the reaction mixture was lowered to 40°C, and 7.9 parts by mass of triethylamine were added. After stirring for 1 hour as is, an appropriate amount of water was added to prepare a block isocyanate-based crosslinking agent (B-1) solution with a solid content of 40 mass%. The acid value of the solid content of crosslinking agent B-1 was 37.6 mgKOH / g.
[0117] (Synthesis of crosslinking agent B-2)
[0118] In a flask equipped with a stirrer, a thermometer, and a reflux condenser, 66.6 parts by mass of a polyisocyanate compound having an isocyanurate structure made from hexamethylene diisocyanate (Duranate TPA, manufactured by Asahi Kasei Chemicals) and 17.5 parts by mass of N-methylpyrrolidone were added dropwise with 21.7 parts by mass of 3,5-dimethylpyrazole, and maintained at 70°C for 1 hour under a nitrogen atmosphere. Afterward, 9.0 parts by mass of dimethylolpropionic acid were added dropwise. The infrared spectrum of the reaction mixture was measured, and after confirming that the absorption of the isocyanate group had disappeared, 6.3 parts by mass of N,N-dimethylethanolamine were added. After stirring for 1 hour, an appropriate amount of water was added, and a block isocyanate-based crosslinking agent (B-2) solution with a solid content of 40% by mass was prepared. The acid value of the solid content of crosslinking agent B-2 was 41.2 mgKOH / g.
[0119] (Synthesis of crosslinking agent B-3)
[0120] 150.0 parts by mass of water and 250.0 parts by mass of methoxypropyl alcohol were added to a flask equipped with a stirrer, a thermometer, and a reflux condenser, and heated to 80°C under a nitrogen atmosphere. Then, a monomer mixture comprising 126.0 parts by mass of methyl methacrylate, 210.0 parts by mass of 2-isopropenyl-2-oxazoline, and 53.0 parts by mass of triethylamine methacrylate, and a polymerization initiator solution comprising 18.0 parts by mass of 2,2'-azobis(2-amidinopropane) dihydrochloride and 170.0 parts by mass of water as a polymerization initiator were each added dropwise from a dropping funnel under a nitrogen atmosphere while maintaining the flask at 80°C over a period of 2 hours. After the dropping was finished, the mixture was stirred at 80°C for 5 hours and then cooled to room temperature. An appropriate amount of water was added to prepare a solution of oxazoline-based crosslinking agent (B-3) with a solid content of 40 mass%. The acid value of the solid content of crosslinking agent B-3 was 39.8 mgKOH / g.
[0121] (Polymerization of crosslinking agent B-4)
[0122] 65.0 parts by mass of a polyisocyanate compound having an isocyanurate structure made from hexamethylene diisocyanate (Duranate TPA, manufactured by Asahi Kasei Chemicals), 17.5 parts by mass of N-methylpyrrolidone, 29.2 parts by mass of 3,5-dimethylpyrazole, and 21.9 parts by mass of polyethylene glycol monomethyl ether with a number average molecular weight of 500 were added to a flask equipped with a stirrer, a thermometer, and a reflux condenser, and maintained at 70°C for 2 hours under a nitrogen atmosphere. Afterward, 4.0 parts by mass of trimethylolpropane were added dropwise. The infrared spectrum of the reaction mixture was measured, and after confirming that the absorption of the isocyanate groups had disappeared, 280.0 parts by mass of water were added. After adding an appropriate amount of water, a block polyisocyanate-based crosslinking agent (B-4) solution with a solid content of 40% by mass was prepared. The acid value of the solid content of crosslinking agent B-4 was 0.0 mgKOH / g.
[0123] (Polymerization of crosslinking agent B-5)
[0124] In a flask equipped with a stirrer, a thermometer, and a reflux condenser, 66.04 parts by mass of a polyisocyanate compound having an isocyanurate structure made from hexamethylene diisocyanate (Duranate TPA, manufactured by Asahi Kasei Chemicals) and 17.50 parts by mass of N-methylpyrrolidone were added dropwise to 25.19 parts by mass of 3,5-dimethylpyrazole, and the mixture was maintained at 70°C for 1 hour under a nitrogen atmosphere. Afterward, 5.27 parts by mass of dimethylolpropionic acid were added dropwise. After measuring the infrared spectrum of the reaction mixture and confirming that the absorption of the isocyanate group had disappeared, 5.59 parts by mass of N,N-dimethylethanolamine and 132.5 parts by mass of water were added. An appropriate amount of water was added to prepare a block polyisocyanate-based crosslinking agent (B-5) solution with a solid content of 40% by mass. The acid value of the solid content of crosslinking agent B-5 was 22.8 mgKOH / g.
[0125] (Synthesis of crosslinking agent B-6)
[0126] 59.5 parts by mass of hexamethylene diisocyanate, 6.8 parts by mass of neopentyl glycol, 16.6 parts by mass of dimethylolbutanoic acid, and 20.0 parts by mass of N-methylpyrrolidone as a solvent were added to a flask equipped with a stirrer, a thermometer, and a reflux condenser, and the mixture was stirred at 80°C for 3 hours under a nitrogen atmosphere, and it was confirmed that the reaction mixture had reached a predetermined amine equivalent. Subsequently, 30.3 parts by mass of 2-butanone oxime were added dropwise to the reaction mixture, and the mixture was maintained at 80°C for 1 hour under a nitrogen atmosphere. Afterward, the infrared spectrum of the reaction mixture was measured, and after confirming that the absorption of the isocyanate group had disappeared, the temperature of the reaction mixture was lowered to 40°C, and 11.9 parts by mass of triethylamine were added. After stirring for 1 hour as is, an appropriate amount of water was added to prepare a block isocyanate-based crosslinking agent (B-6) solution with a solid content of 40 mass%. The acid value of the solid content of crosslinking agent B-6 was 55.4 mgKOH / g.
[0127] (Manufacture of Polyester Resin C-1)
[0128] 194.2 parts by mass of dimethyl terephthalate, 184.5 parts by mass of dimethyl isophthalate, 14.8 parts by mass of dimethyl-5-sodium sulfoisophthalate, 233.5 parts by mass of diethylene glycol, 136.6 parts by mass of ethylene glycol, and 0.2 parts by mass of tetra-n-butyl titanate were added to a stainless steel autoclave equipped with a stirrer, a thermometer, and a partial reflux condenser, and an ester exchange reaction was carried out for 4 hours at a temperature of 220°C starting from 160°C. Subsequently, the temperature was raised to 255°C, the reaction system was gradually depressurized, and the reaction was carried out for 1 hour and 30 minutes under a reduced pressure of 30 Pa to obtain a copolymerized polyester resin (C-1). The obtained polyester resin (C-1) was pale yellow and transparent. The reduction viscosity of the polyester resin (C-1) was measured to be 0.70 dl / g.
[0129] In addition, 15 parts by mass of polyester resin (C-1) and 15 parts by mass of ethylene glycol n-butyl ether were placed in a reactor equipped with a stirrer, a thermometer, and a reflux device, and the resin was dissolved by heating and stirring at 110°C. After the resin was completely dissolved, 70 parts by mass of water were slowly added to the polyester solution while stirring, and after addition, the liquid was cooled to room temperature while stirring. An appropriate amount of water was added to prepare a polyester resin (C-1) solution with a solid content of 30% by mass. The acid value of the solid content of polyester resin C-1 was 0.9 mgKOH / g.
[0130] (Manufacture of Polyester Resin C-2)
[0131] 194.2 parts by mass of dimethyl terephthalate, 194.2 parts by mass of dimethyl isophthalate, 233.5 parts by mass of diethylene glycol, 136.6 parts by mass of ethylene glycol, and 0.2 parts by mass of tetra-n-butyl titanate were added to a stainless steel autoclave equipped with a stirrer, a thermometer, and a partial reflux condenser, and an ester exchange reaction was carried out for 4 hours at a temperature of 160°C to 220°C. Subsequently, the temperature was raised to 255°C, the pressure of the reaction system was gradually reduced, and the reaction was carried out for 1 hour under a reduced pressure of 30 Pa. Additionally, nitrogen was introduced into the system to release the reduced pressure, and the system was cooled to 200°C. 28.0 parts by mass of trimellitic anhydride were added to the system while stirring, and an additional reaction was carried out for 2 hours to obtain a polyester resin (C-2). The obtained polyester resin (C-2) was pale yellow and transparent. The reduction viscosity of the polyester resin (C-2) was measured to be 0.35 dl / g.
[0132] In addition, 15 parts by mass of polyester resin (C-2) and 15 parts by mass of tetrahydrofuran were placed in a reactor equipped with a stirrer, a thermometer, and a reflux device, and the resin was dissolved by heating and stirring at 70°C. After the resin was completely dissolved, 31 parts by mass of triethylamine and 70 parts by mass of water were slowly added to the polyester solution while stirring. After addition, the pressure in the system was reduced to remove the tetrahydrofuran, and the solution was cooled to room temperature. An appropriate amount of water was added to prepare a polyester resin (C-2) solution with a solid content of 30% by mass. The acid value equivalent to the solid content of polyester resin C-2 was 37.4 mgKOH / g.
[0133] (Manufacture of Acrylic Resin D-1)
[0134] Forty parts of propylene glycol monomethyl ether were placed in a flask equipped with a stirrer, a thermometer, and a reflux condenser, and heated and maintained at 100°C. A mixture of 60.0 parts by mass of normal butyl acrylate, 42.0 parts by mass of methyl methacrylate, 2.9 parts by mass of 2-hydroxyethyl methacrylate, 5.7 parts by mass of acrylic acid, and 5 parts by mass of azobisisobutyronitrile was added dropwise over a period of 3 hours. After adding, the mixture was aged at the same temperature for 2 hours. Subsequently, the reaction mixture was cooled to 40°C, and 8.4 parts by mass of triethylamine and 165 parts by mass of water were added while stirring. After stirring for 1 hour, an appropriate amount of water was added to prepare an acrylic resin (D-1) solution with a solid content of 35% by mass. The acid value of the solid content of this acrylic resin D-1 was 40.1 mgKOH / g.
[0135] (Manufacture of Polyester Resin E-1 for Base)
[0136] (Preparation of Antimony Trioxide Solution)
[0137] Antimony trioxide (manufactured by Sigma Aldrich Japan Kodo Kaisha) was added to a flask together with ethylene glycol, stirred at 150°C for 4 hours to dissolve, then cooled to room temperature to prepare an ethylene glycol solution of 20 g / l antimony trioxide.
[0138] (Polymerization of base polyester resin E-1)
[0139] High-purity terephthalic acid and twice the molar amount of ethylene glycol were introduced into a 2-liter stainless steel autoclave equipped with a stirrer, and 0.3 mol% of triethylamine was added relative to the acid component. An esterification reaction was carried out at 250°C under a pressure of 0.25 MPa while removing water from the system through distillation, thereby obtaining a mixture of bis(2-hydroxyethyl)terephthalate and oligomers with an esterification rate of approximately 95% (hereinafter referred to as the BHET mixture). To this BHET mixture, the above antimony trioxide solution was used as a polycondensation catalyst and added to the polyester at a concentration of 0.04 mol% as antimony atoms relative to the acid component. Subsequently, the mixture was stirred at 250°C for 10 minutes under a nitrogen atmosphere and at atmospheric pressure. After that, the temperature was raised to 280°C over 60 minutes while the pressure of the reaction system was gradually lowered to 13.3 Pa (0.1 Torr), and a polycondensation reaction was further carried out at 280°C and 13.3 Pa for 68 minutes, and polyester resin E-1 was obtained having an intrinsic viscosity (IV) (solvent: phenol / tetrachloroethane = 60 / 40) of 0.61 dl / and substantially no particles.
[0140] (Manufacture of Polyester Resin E-2 for Base)
[0141] (Preparation example of an aluminum compound solution)
[0142] An equal amount (volume ratio) of ethylene glycol was added to a 20 g / l aqueous solution of basic aluminum acetate (hydroxyaluminum diacetate; manufactured by Sigma Aldrich Japan Kodo Kaisha) and stirred at room temperature for 6 hours. Then, water was distilled off from the system while stirring at 70 to 90°C for several hours under reduced pressure (133 Pa), and an ethylene glycol solution of 20 g / l of aluminum compound was prepared.
[0143] (Example of preparation of a phosphorus compound solution)
[0144] 3,5-di-tert-butyl-4-hydroxybenzylphosphonic acid diethyl (Irganox 1222 (BASF)) was added to a flask along with ethylene glycol, heated at a liquid temperature of 160°C for 25 hours while stirring under nitrogen purging, and an ethylene glycol solution of 50 g / l of phosphorus compound was prepared.
[0145] (Preparation of a mixture of a solution of an aluminum compound and a solution of a phosphorus compound)
[0146] Each ethylene glycol solution obtained from the above-mentioned preparation example of the aluminum compound and the above-mentioned preparation example of the phosphorus compound was put into a flask, mixed at room temperature so that the molar ratio of aluminum atoms to phosphorus atoms was 1:2, and stirred for 1 day to prepare a catalyst solution.
[0147] (Polymerization of base polyester resin E-2)
[0148] Polyester resin E-1 was polymerized in the same manner as polyester resin E-2, except that instead of the antimony trioxide solution as a polycondensation catalyst, a mixture of the aforementioned aluminum compound solution and phosphorus compound solution was used and added such that the aluminum atoms and phosphorus atoms were 0.014 mol% and 0.028 mol%, respectively, relative to the acid component in the polyester. However, by making the polymerization time 68 minutes, polyester resin E-2 was obtained with an intrinsic viscosity (IV) of 0.61 dl / and substantially no particles.
[0149] (Example 1)
[0150] (1) Adjustment of the coating solution
[0151] A coating agent was mixed into a mixed solvent of water and isopropanol (80 / 20 mass ratio) and the following coating agent was mixed to prepare a coating solution in which the solid mass ratio of the polyurethane resin (A-1) solution / crosslinking agent (B-1) solution was 70 / 30.
[0152] 78.26 parts by mass of mixed solvent (water / isopropanol)
[0153] 14.00 parts by mass of polyurethane resin (A-1) solution
[0154] 5.25 parts by mass of crosslinking agent (B-1) solution
[0155] Particle I 0.12 parts by mass
[0156] (Silica sol with average particle size of 100 nm, solid content 40 mass%)
[0157] Particle II 1.87 parts by mass
[0158] (Silica sol with an average particle size of 40 to 50 nm, solid content 30 mass%)
[0159] 0.50 parts by mass of surfactant
[0160] (Silicon-based, solid content 10 mass%)
[0161] (2) Manufacturing of laminated polyester film
[0162] As a film raw material polymer, resin pellets of polyester resin E-1 were dried at 135°C for 6 hours under a reduced pressure of 133 Pa. Afterwards, the pellets were fed into an extruder and melt-extruded into a sheet at approximately 280°C, and then rapidly cooled and solidified on a rotary cooling metal roll maintained at a surface temperature of 20°C to obtain an unoriented PET sheet.
[0163] This unoriented PET sheet was heated to 100°C using a heated roll group and an infrared heater, and then stretched 3.5 times in the longitudinal direction using a roll group with a peripheral speed difference to obtain a uniaxially stretched PET film.
[0164] Next, the above coating solution was applied to one side of the PET film such that the final coating amount after drying (after biaxial stretching) was 0.13 g / m². After drying the coating solution, it was stretched 4.0 times in the width direction at 110°C, and then heated at 230°C for 5 seconds while the width direction of the film was fixed. Additionally, a 3% relaxation treatment in the width direction was performed to obtain a laminated polyester film of 100 μm. The evaluation results are shown in Table 1.
[0165] (Example 2)
[0166] A laminated polyester film was obtained in the same manner as in Example 1, except that the polyurethane resin was (A-2) and the ratio of the polyurethane resin to the crosslinking agent was changed to 60 / 40 (mass ratio).
[0167] (Example 3)
[0168] A laminated polyester film was obtained in the same manner as in Example 1, except that the polyurethane resin was (A-3) and the ratio of the polyurethane resin to the crosslinking agent was changed to 50 / 50 (mass ratio).
[0169] (Example 4)
[0170] A laminated polyester film was obtained in the same manner as in Example 1, except that the crosslinking agent was (B-2) and the ratio of the polyurethane resin to the crosslinking agent was changed to 60 / 40 (mass ratio).
[0171] (Example 5)
[0172] A laminated polyester film was obtained in the same manner as in Example 1, except that the crosslinking agent was (B-3) and the ratio of polyurethane resin to crosslinking agent was changed to 60 / 40 (mass ratio).
[0173] (Example 6)
[0174] A laminated polyester film was obtained in the same manner as in Example 1, except that a crosslinking agent (B-4) was used in combination with polyurethane resin (A-1) and crosslinking agent (B-1), and the ratio was changed to (A-1) / (B-1) / (B-4)=55 / 35 / 10 (mass ratio).
[0175] (Example 7)
[0176] A laminated polyester film was obtained in the same manner as in Example 1, except that a polyester resin (C-1) was used in combination with a polyurethane resin (A-1) and a crosslinking agent (B-1), and the ratio was changed to (A-1) / (B-1) / (C-1)=36 / 24 / 40 (mass ratio).
[0177] (Example 8)
[0178] A laminated polyester film was obtained in the same manner as in Example 1, except that a polyester resin (C-1) was used in combination with a polyurethane resin (A-1) and a crosslinking agent (B-1), and the ratio was changed to (A-1) / (B-1) / (C-1)=24 / 16 / 60 (mass ratio).
[0179] (Example 9)
[0180] A laminated polyester film was obtained in the same manner as in Example 1, except that resin pellets of polyester resin E-2 were used as the film raw material polymer.
[0181] (Example 10)
[0182] A laminated polyester film was obtained in the same manner as in Example 1, except that the polyurethane resin was changed to (A-8).
[0183] (Comparative Example 1)
[0184] A laminated polyester film was obtained in the same manner as in Example 1, except that only the polyurethane resin (A-1) was used and the crosslinking agent (B-1) was not used.
[0185] (Comparative Example 2)
[0186] A laminated polyester film was obtained in the same manner as in Example 1, except that only the crosslinking agent (B-1) was used and the polyurethane resin (A-1) was not used.
[0187] (Comparative Example 3)
[0188] A laminated polyester film was obtained in the same manner as in Example 1, except that the polyurethane resin was changed to (A-4).
[0189] (Comparative Example 4)
[0190] A laminated polyester film was obtained in the same manner as in Example 1, except that the polyurethane resin was (A-5) and the ratio of the polyurethane resin to the crosslinking agent was changed to 60 / 40 (mass ratio).
[0191] (Comparative Example 5)
[0192] A laminated polyester film was obtained in the same manner as in Example 1, except that the polyurethane resin was (A-6) and the ratio of the polyurethane resin to the crosslinking agent was changed to 50 / 50 (mass ratio).
[0193] (Comparative Example 6)
[0194] A laminated polyester film was obtained in the same manner as in Example 1, except that the polyurethane resin was changed to (A-7) and the crosslinking agent to (B-5).
[0195] (Comparative Example 7)
[0196] A laminated polyester film was obtained in the same manner as in Example 1, except that the crosslinking agent was (B-5) and the ratio of polyurethane resin to crosslinking agent was changed to 75 / 25 (mass ratio).
[0197] (Comparative Example 8)
[0198] A laminated polyester film was obtained in the same manner as in Example 1, except that the crosslinking agent was changed to (B-6).
[0199] (Comparative Example 9)
[0200] A laminated polyester film was obtained in the same manner as in Example 1, except that the polyurethane resin (A-1) was changed to a polyester resin (C-2).
[0201] (Comparative Example 10)
[0202] A laminated polyester film was obtained in the same manner as in Example 1, except that the polyurethane resin (A-1) was changed to an acrylic resin (D-1).
[0203] Table 1 summarizes the evaluation results of each example and comparative example.
[0204] As shown in Table 1, in each example, satisfactory results were obtained regarding haze, blocking resistance, adhesion to UV-curable ink, adhesion to hard coat layer, and moisture and heat resistance. On the other hand, in Comparative Examples 1 to 10, satisfactory results were not obtained in at least any of the evaluation items mentioned above.
[0205] Industrial applicability
[0206] According to the present invention, it is possible to provide a laminated polyester film that can be suitably used in all fields, such as optical applications, packaging applications, and label applications.
Claims
Claim 1 A laminated polyester film having a coating layer, wherein the coating layer is formed from a composition comprising a polyurethane resin having an acid value of 30 to 50 mgKOH / g having a carboxyl group on at least one side of the polyester film and a crosslinking agent having an acid value of 30 to 50 mgKOH / g having a carboxyl group, and wherein the crosslinking agent having a carboxyl group is an oxazoline compound, a carbodiimide compound, an epoxy compound, or an isocyanate compound having a carboxyl group introduced into the molecule. Claim 2 A laminated polyester film according to claim 1, wherein the crosslinking agent having a carboxyl group is an isocyanate compound in which a carboxyl group is introduced into the molecule. Claim 3 A laminated polyester film according to paragraph 2, wherein the isocyanate compound having a carboxyl group introduced into the molecule is a block isocyanate compound having a carboxyl group introduced into the molecule. Claim 4 A laminated polyester film according to claim 1, wherein the polyurethane resin having carboxyl groups is a urethane resin synthesized with at least a carboxyl group-containing polyol component and a polyisocyanate component, and additionally a chain extender as needed. Claim 5 A laminated polyester film according to claim 4, wherein the carboxyl group-containing polyol component is at least one selected from the group consisting of carboxyl group-containing polyalkylene glycol, carboxyl group-containing acrylic polyol, carboxyl group-containing polyolefin polyol, carboxyl group-containing polyester polyol, 2,2-dimethylolpropionic acid, 2,2-dimethylolbutanoic acid, 2,2-dimethylolbutyric acid, and 2,2-dimethylolvaleric acid. Claim 6 A laminated polyester film according to claim 4, wherein the polyisocyanate component is at least one selected from the group consisting of aliphatic diisocyanates having an aromatic ring, alicyclic diisocyanates, and aliphatic diisocyanates. Claim 7 A laminated polyester film according to claim 1, wherein the weight ratio of a polyurethane resin having carboxyl groups and a crosslinking agent having carboxyl groups in the composition is 90 / 10 to 10 / 90. Claim 8 A laminated polyester film according to claim 1, wherein the composition further comprises a polyester resin. Claim 9 A laminated polyester film according to claim 8, wherein the polyester resin comprises a dicarboxylic acid and a diol having a branched structure or a diol having one or more ether bonds. Claim 10 A laminated polyester film according to claim 1, wherein the thickness of the coating layer is in the range of 0.001 to 2.00 μm. Claim 11 A laminated polyester film according to claim 1, wherein the haze of the laminated polyester film is 2.5% or less. Claim 12 A laminated polyester film having a UV-curing resin on a coating layer of the laminated polyester film in claim 1. Claim 13 A method for manufacturing a laminated polyester film having a coating layer as described in claim 1, comprising the steps of: applying a composition comprising a polyurethane resin having an acid value of 30 to 50 mgKOH / g having a carboxyl group and a crosslinking agent having an acid value of 30 to 50 mgKOH / g having a carboxyl group to at least one side of the polyester film, and heat treating to form a coating layer, wherein the crosslinking agent having an acid value of 30 to 50 mgKOH / g having a carboxyl group is an oxazoline compound, a carbodiimide compound, an epoxy compound, or an isocyanate compound having a carboxyl group introduced into its molecule.
Citation Information
Patent Citations
Easily adhesive white polyester film for solar cell
JP2011140124A
Laminated polyester film
JP2016216655A
Aqueous resin composition and laminated body and article employing same
WO2019131414A1
Laminated polyester film
KR1020130057968A
Laminated film
KR1020170121175A
